SPARC the Change: What the Strategic Purchasing Africa Resource Center Has Learned about Improving Strategic Health Purchasing in Africa - Cheryl Cashin; George Kimathi; Nathaniel Otoo; Danielle Bloom; Agnes Gatome-Munyua (Taylor & Francis Group, 2022)
ABSTRACTEmbodied in the goals of universal health coverage (UHC) are societal norms about ethics, equity, solidarity, and social justice. As African countries work toward UHC, it is important for their governments to use all available resources, knowledge, and networks to continue to bring this goal closer to reality for their populations. The Strategic Purchasing Africa Resource Center (SPARC) was established in 2018 as a "go-to" source of Africa-based expertise in strategic health purchasing, which is a critical policy tool for making more effective use of limited funds for UHC. SPARC facilitates collaboration among governments and research partners across Africa to fill gaps in knowledge on how to make progress on strategic purchasing. The cornerstone of this work has been the development and use of the Strategic Health Purchasing Progress Tracking Framework to garner insights from each country's efforts to make health purchasing more strategic. Application of the framework and subsequent dialogue within and between countries generated lessons on effective purchasing approaches that other countries can apply as they chart their own course to use strategic purchasing more effectively. These lessons include the need to clarify the roles of purchasing agencies, define explicit benefit packages as a precondition for other strategic purchasing functions, use contracting to set expectations, start simple with provider payment and avoid open-ended payment mechanisms, and use collaborative rather than punitive provider performance monitoring. SPARC has also facilitated learning on the "how-to" and practical steps countries can take to make progress on strategic purchasing to advance UHC.